Roles of LINC01473 and CD74 in osteoblasts in multiple myeloma bone disease. (June 2022) - Peng, Fengping; Yan, Siyang; Liu, Hui; Liu, Zhaoyun; Jiang, Fengjuan; Cao, Panpan; Fu, Rong
The suppression of osteoblast (OB) activity is partially responsible for multiple myeloma (MM) bone disease. Long non-coding RNAs (lncRNAs) play a vital role in bone formation and resorption. However, their functions in OBs from patients with MM have rarely been reported. Through high-throughput sequencing of OBs from patients with MM and healthy controls, we identified several lncRNAs and messenger RNAs (mRNAs) with different expression profile and validated them using quantitative real-time PCR. In total, 22 upregulated and 21 downregulated lncRNAs were found in OBs from patients with MM. Moreover, 18 upregulated protein-coding mRNAs were identified. The expression levels of LINC01473 and its associated co-expression mRNA, CD74, were higher in patients with MM than in healthy controls (p=0.047 and p=0.016, respectively). LINC01473 expression demonstrated a negative correlation with serum interleukin-2 and tumor necrosis factor α levels, whereas the expression of mRNA CD74 was positively associated with serum lactic dehydrogenase in patients with MM. Aberrant expression of lncRNAs and mRNAs was observed in OBs from patients with MM. This study identifies new promising targets for further research on imbalanced bone formation and resorption and MM immune escape.